Constructing Solidarity for a Liberative Ethic - Day, T. author. aut Link
XIX, 204 p.
Keywords: Constructing Solidarity offers a critical path toward the transformation of white worldviews, theologies, ethics, and praxis for scholars, activists, religious leaders, and those seeking guidance.